Calcium Nitrate Toxicity on Rat Liver and Kidney Functions: A Biochemical and Histopathological Evaluation - Araar, S; Khaldi, F; Sayah, S; Chaib, S; Gheid, A. (My University, 2022)
Calcium NitrateTetrahydrate is a wide-used nitrogen fertilizer in Algerian agriculture. The present study was aimed to examine the toxic effects of calcium nitrate on kidney and liver functional biochemical markers. Twenty-eight male albino wistar male rats were divided into three treated groups receiving orally 200, 400 and 800mg/kg of calcium nitrate, and one untreated control group. Results showed a dose- dependent increase in kidney and liver relative weights, serum levels of glucose, cholesterol, triglyceride, blood urea, creatinine, and uric acid, and enzymatic activity of transaminases and alkaline phosphatase. However, serum protein and albumin levels were significantly decreased in a dose dependent manner as compared with those of control group. In addition, hepatic and renal histological changes were evidenced by hepatocyte degeneration, necrosis, dilation and sinusoid congestion, atrophy of glomeruli, vascular congestion, and infiltration of inflammatory cells. It is noteworthy that these adverse stress effects were higher in 400 and 800 mg/kg calcium nitrate treated rats than those treated with 200mg/kg and control group. In conclusion, the study proved the effective ability of subacute exposure of calcium nitrate to induce liver and kidney stress dysfunctions